Effects of Humidity on Gessoes for Easel Paintings. Issue 1656 (22nd August 2014) - Doutre, Michael; Murray, Alison; Fuster-López, Laura
ABSTRACT: Gessoes are widely used in easel painting as grounds or preparatory layers; in art conservation, gessoes are employed as infill materials to level a loss in the paint surface in preparation for inpainting. The goal of this investigation was to establish the relationship between the mechanical behavior of various gessoes when exposed to different relative humidities (25%, 50%, and 100%) and to compare modern commercial gesso products with a traditional gesso. The materials included two commercial artists' acrylic gessoes (composed of largely titanium dioxide and aqueous dispersions of acrylic polymers), two commercial spackling compounds frequently used in the conservation of easel paintings, and a traditional gesso (calcium carbonate and rabbit skin glue). Uniaxial tensile testing was used to characterize the elastic modulus, strain at failure, and ultimate tensile strength (UTS) of the materials. By understanding the physical limits of these materials under different conditions, damage to artworks and the failure of conservation treatments containing these types of materials may be prevented or reduced.